Price forecasting of mustard using ARIMA and EGARCH models (Journal of Oilseed Brassica, 2026)
Autoregressive Integrated Moving Average (ARIMA) and Exponential GARCH (EGARCH) model was studied along with their estimation procedures for modelling and forecasting of mustard price. For forecasting mustard price ARIMA (0,1,1) model is used which gives reasonable and acceptable forecasts but the study has revealed that the AR(1)-EGARCH(1,1) model outperformed the price forecasting models for mustard prices primarily due to its ability to capture asymmetric volatility pattern.